Development of a low priming volume hydrodynamic test bench for isolated ex vivo perfusion of small animal lungs - O. Yu. Esipova; A. P. Kuleshov; V. K. Bogdanov; A. S. Esipov; E. A. Volkova; N. V. Grudinin (Вестник трансплантологии и искусственных органов)
Objective: to develop and validate a hydrodynamic test bench (HTB) with a small filling volume for ex vivo normothermic machine perfusion (NMP) of donor lungs of small experimental animals (rats) using the open- loop technique.Materials and methods. An HTB was developed for ex vivo NMP of donor lungs of rats. It is a prefabricated structure with stands that hold the following equipment: a ventilator for small laboratory animals, a heating element, a low priming volume membrane oxygenator and a dome for donor lung storage, as well as roller peristaltic pump, sensors and device for invasive pressure measurement in the circuit, bubble filter and a line kit. Wistar rats (n = 6) were used to investigate the effectiveness of the HTB. Following the removal of donor lungs, the graft was positioned on the HTB and ex vivo lung perfusion (EVLP) was initiated with selected parameters. During the rat donor lung perfusion procedure, ex vivo PaO2/FiO2 ratio, oxygenation index (OI), pulmonary artery pressure (PAP) and peripheral pulmonary vascular resistance (pPVR) were measured.Results. High OI values were obtained at the end of the procedure (460 ± 32 at p = 0.028); constant PAP values were recorded in all cases throughout the EVLP procedure – from 9.13 to 7.93 mmHg at p > 0.05. The criterion for HTB functionality was pPVR, which tended to decrease in all cases – from 603.3 ± 56 to 89.1 ± 15 dynes/sec/cm–5 at p = 0.000. No design flaws impacting the donor lungs’ functional condition during ex vivo NMP procedure were found in the circuit of the hydrodynamic low priming volume bench during experimental studies.Conclusion. The efficiency and technical functionality of the HTB were demonstrated by the results of the experimental study conducted on the laboratory animals, rats. The observed dynamics of decrease in pPVR and the high OI values at stable PAP allowed for the conclusion that both the ex vivo perfusion itself and the technical design of the HTB are efficient.